MicroRNA miR-502-5p inhibits ovarian cancer genesis by downregulation of GINS complex subunit 2. Issue 1 (1st January 2021) - Zhan, Lili; Yang, Jing; Liu, Yang; Cheng, Yanxiang; Liu, Hua
ABSTRACT: Ovarian cancer (OC) is one of the most common malignancies with high incidence and mortality and the eighth most common cancer-associated mortality in women worldwide. Aberrant expression of the GINS complex subunit 2 (GINS2) gene and miR-502-5p has been associated with cancer progression. This study aims to investigate the specific molecular mechanism of the miR-502-5p-GINS2 axis in OC. GINS2 and miR-502-5p expression in OC tissues and cell lines was measured using RT-qPCR. Next, we investigated the interaction between miR-502-5p and GINS2 using a luciferase assay. The role of the miR-502-5p-GINS2 axis was detected by assessing cell proliferation, migration, and apoptosis levels, such as caspase-3 activity and caspase-3 protein expression, in the OC cell lines CaOV3 and SKOV3, respectively. MiR-502-5p expression was decreased, and GINS2 expression was dramatically elevated in OC tissues and cells. Upregulation of miR-502-5p expression repressed cellular proliferation and migration levels but increased the cellular apoptosis level. GINS2 overexpression enhanced the proliferation and migration levels but hampered OC cell apoptosis. Moreover, miR-502-5p inhibited GINS2 expression and suppressed OC tumorigenesis. miR-502-5p targeting GINS2 suppressed OC progression by inhibiting cell growth and promoting cell apoptosis. Hence, we provide a comprehensive understanding of OC involving both miR-502-5p and GINS2, which might be effective therapeutic targets for OC patients. Graphical Abstract: uf0001